2010
DOI: 10.1161/circulationaha.109.906610
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Mitochondrial Fission Protects the Heart Against Ischemia/Reperfusion Injury

Abstract: Background-Whether alterations in mitochondrial morphology affect the susceptibility of the heart to ischemia/ reperfusion injury is unknown. We hypothesized that modulating mitochondrial morphology protects the heart against ischemia/reperfusion injury. Methods and Results-In response to ischemia, mitochondria in HL-1 cells (a cardiac-derived cell line) undergo fragmentation, a process that is dependent on the mitochondrial fission protein dynamin-related protein 1 (Drp1). Transfection of HL-1 cells with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
829
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 856 publications
(895 citation statements)
references
References 29 publications
56
829
4
6
Order By: Relevance
“…Loss of Mfn2 also delayed membrane depolarization in isolated cardiomyocytes from adult Mfn2 −/− mice, leading to the suggestion that Mfn2 may function to control mitochondrial permeability transition pore opening (Papanicolaou et al, 2011). Similarly, cardiac‐specific deletion of Mfn2 produced dissipation of mitochondrial membrane potential and elevated ROS production (Chen et al, 2012), whilst overexpression of Mfn2 was found to increase the percentage of cells containing elongated mitochondria, thereby reducing mitochondrial permeability transition pore opening and cell death after simulated ischaemia/reperfusion injury (Ong et al, 2010). It also appears that Mfn2 serves an essential role in maintaining mitochondrial coenzyme Q levels in mouse hearts, thereby promoting optimal function of the respiratory chain (Mourier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Mfn2 also delayed membrane depolarization in isolated cardiomyocytes from adult Mfn2 −/− mice, leading to the suggestion that Mfn2 may function to control mitochondrial permeability transition pore opening (Papanicolaou et al, 2011). Similarly, cardiac‐specific deletion of Mfn2 produced dissipation of mitochondrial membrane potential and elevated ROS production (Chen et al, 2012), whilst overexpression of Mfn2 was found to increase the percentage of cells containing elongated mitochondria, thereby reducing mitochondrial permeability transition pore opening and cell death after simulated ischaemia/reperfusion injury (Ong et al, 2010). It also appears that Mfn2 serves an essential role in maintaining mitochondrial coenzyme Q levels in mouse hearts, thereby promoting optimal function of the respiratory chain (Mourier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…10b, upper panel) and apoptosis ( Supplementary Fig. 10b, lower ARTICLE and heart failure 6,7 . Thus, it is necessary to elucidate the molecular mechanisms of mitochondrial regulation, and discover potential therapeutic targets for inhibiting myocardial infarction and the consequent heart failure.…”
Section: Pink1 Inhibits Mitochondrial Fragmentation and Apoptosismentioning
confidence: 99%
“…For example, knockdown of Drp1 inhibits mitochondrial fragmentation and p53-dependent apoptosis 7,37 . Enforced expression of Mfn2 leads to mitochondrial fusion that is important for cell survival 38 .…”
Section: Pink1 Inhibits Mitochondrial Fragmentation and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of cardiac diseases, mitochondria exhibit the abnormal morphology with a small size and fragmentation because of excess fission (Schaper et al, 1991;Hom and Sheu, 2009). A recent research demonstrates that the pharmacological inhibition of the mitochondrial fission protein Drp1 can protect adult murine cardiomyocytes against ischemia/reperfusion injury and reduce myocardial infarct size in the murine heart (Ong et al, 2010). Another research reveals that mitochondria in the neonatal and adult cardiomyocytes undergo rapid and transient fragmentation in response to thapsigargin-or KCl-induced cytosolic calcium increase (Hom et al, 2010).…”
Section: Mitochondria and Heart Diseasesmentioning
confidence: 99%